Biomimetic Light‐Driven Aerogel Passive Pump for Volatile Organic Pollutant Removal. Issue 11 (23rd February 2022) - Drdova, Sarka; Zhao, Shanyu; Giannakou, Marianna; Sivaraman, Deeptanshu; Guerrero‐Alburquerque, Natalia; Bonnin, Anne; Pauer, Robin; Pan, Zhengyuan; Billeter, Emanuel; Siqueira, Gilberto; Zeng, Zhihui; Koebel, Matthias M.; et al.
Abstract: Inspired by the solar‐light‐driven oxygen transportation in aquatic plants, a biomimetic sustainable light‐driven aerogel pump with a surface layer containing black manganese oxide (MnO2 ) as an optical absorber is developed. The flow intensity of the pumped air is controlled by the pore structure of nanofilbrillated cellulose, urea‐modified chitosan, or polymethylsilsesquioxane (PMSQ) aerogels. The MnO2 ‐induced photothermal conversion drives both the passive gas flow and the catalytic degradation of volatile organic pollutants. All investigated aerogels demonstrate superior pumping compared to benchmarked Knudsen pump systems, but the inorganic PMSQ aerogels provide the highest flexibility in terms of the input power and photothermal degradation activity. Aerogel light‐driven multifunctional gas pumps offer a broad future application potential for gas‐sensing devices, air‐quality mapping, and air quality control systems. Abstract : Porous aerogels facilitate a passive gas flow under an applied thermal gradient based on the thermal transpiration process. This study demonstrates the operation of a bilayer aerogel pump with a top layer containing a light absorber with catalytic properties. Therefore, irradiation is used as a sole power input to pump and degrade airborne organic pollutants simultaneously.